The benefits of physical activity for depression (International Seven Journal of Health Research, 2024)
Depression is an affective disorder present throughout human history, characterized by feelings of sadness, pessimism and low self-esteem. Medical care is essential for proper diagnosis and treatment. Estimates suggest that more than 300 million people worldwide suffer from depression, which differs from normal mood fluctuations. When chronic and intense, it can cause great suffering and dysfunction, and can even lead to suicide. With around 800,000 deaths by suicide every year, depression is one of the leading causes of death among young people. Regular physical activity is considered by some scientists to be one of the best antidepressants, bringing a range of benefits for mental and emotional health.